Análise teórica e experimental do comportamento de um trocador de calor geotérmico - Martins, William Marques (Universidade do Vale do Rio dos Sinos, 2015)
This work presents a theoretical and experimental study of a coil-type geothermal heat exchanger, water-soil, for use as condenser in an air conditioning system. An experimental bench was constructed to analyses the heat exchanger performance. This experimental facility consists of a thermal reservoir, a water pump and flow meter, a helical heat exchanger with length and diameter of 3 m and 0.27, respectively and buried vertically at this depth. During the experiments were monitored the temperatures in seven points: four in the heat exchanger and three for measuring the soil temperatures at three different depths. The results obtained with the experiments were used to obtain the thermal conductivity of the soil. The same data were used to validated the theoretical model that was implemented in the EES platform. The difference between the measured heat transfer rate and the theoretical results was about 1%. The model was also used to determine the required length of the heat exchanger to suit a particular thermal power demand for the replacement of a condenser of an air conditioning system. For this, we used the data from a split type air conditioning unit, with a condenser thermal capacity of 3,52 kW, and to analyze the behavior of the heat exchanger with various design conditions, coming to a calculated depth 37.11 meters to meet this demand.
Keywords: Trocador de calor geotérmico; Bomba de calor; Condicionador de ar; Temperatura do solo; Geothermal heat exchanger; Heat pump; Air conditioning; Soil temperatures; ACCNPQ::Engenharias::Engenharia Mecânica